(untitled) (Società e diritti, 2022)
Giuseppe Toniolo is a man of his time. Economist, engaged in politics, operating between the end of the 19th century and the beginning of the 20th century, he was raised to the honors of the altars in 2012 by Pope Benedict XVI, who highlighted its relevance and modernity. For years forgotten because it is not in line with the dominant culture, Domenico Sorrentino, with an important and complex reconstructive work of the entire thought, has proposed an interesting reading in a modern key. In this work we try to deepen not so much the economist Toniolo as the politician, advocate of a democratic society founded on popularism. Can this social construction be a response to the populism that seems to characterize the politics of our times? Can the crisis of representative democracy and parties find current answers in Toniolo?